Metode Jigsaw dan Kepercayaan Diri Siswa dalam Pembelajaran Bahasa Arab - Hamid, Fajrur Rahman; Shodiq, Muh Fajar; Qosim, Muh Nanang (An-Nuqthah, 2023)
Confidence will allow students to learn Arabic to the fullest. But is the self-confidence built in the classroom in accordance with the jigsaw theory? This research oriented to explain how the process of learning Arabic at MTs Sadamiyyah Jepara by using a jigsaw was in accordance with jigsaw theory and whether it was able to increase students' self-confidence. This type of research was qualitative research. The results of this study found that the application of jigsaw in Arabic learning was in accordance with the theory and could prove that the application of jigsaw in Arabic learning was able to increase students' self-confidence. Through these results Jigsaw can be used to develop students' confidence in learning Arabic.